A, Ths THE INFLUENCE OF INTERNATIONAL CRIMINAL LAW ON NATIONAL CRIMINAL LAW - Muhammad Rayhan Rayhan; Faizal Hidayatallah Widjajanto Faizal; Raihan Setia Gilbranza Setia; Archi Cautsa Jaya Archi; Gregorius Ringo Putra Wibowo Grey (International Journal of Law and Legal Ethics, 2023)
International criminal law is not part of criminal law, but in fact international criminal law is one source of the development of criminal law. As a form of international criminal law, international agreements generally affect legal values, legal principles, and national criminal law norms. This study tries to explain the position of international criminal law in domestic criminal law and to determine the influence of international criminal law on domestic criminal law. The research methodology used in this study is a prescriptive legal research methodology. These results indicate that the relationship between international criminal law and domestic law is complementary.